PERANCANGAN SIMULASI PERGERAKAN AUTOMATIC CEILING SUSPENSION UNTUK ALAT RONTGEN STASIONER - Dewa Gde Ardha Putra; Irawadi Buyung; Sri Lestari (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2017)
Ceiling suspension stand is a method of x-ray tube placement on a stationary x- ray apparatus by hanging on the ceiling of the examination room and can be moved horizontally or vertically using a rail as a track. Simulating the movement of Automatic Ceiling Suspension for Stationary X-ray Equipment was made to produce an automatic movement of the ceiling suspension system used on stationary x-ray apparatus. Simula- tions created will facilitate x-ray equipment operator when setting the position of the x-ray tube during the examination. Simulations using a dc motor as the prime mover which is divided into horizontal and vertical movement. The movement of the motor is controlled by a microcontroller as a command center in the simulation. The movement generated by the simulation in the form of transfer of the parking position toward the examination table, the parking position to the vertical bucky, a vertical bucky toward the examining table po- sition, and vertical bucky towards the parking position. The test results of simulation crea- ted is 8 seconds to move from the parking position to the position of the examination ta- ble, 38 seconds to move from the parking position to the vertical bucky.